Polymorphisms of the vitamin D receptor gene and the risk of inflammatory bowel disease: a meta-analysis - L. Wang; Z.T. Wang; Jiajia Hu; Rong Fan; Jianping Zhou; J. Zhong (2014)
The gene encoding vitamin D receptor (VDR) is recognized as a promising candidate for indicating the development of inflammatory bowel disease (IBD).Four genetic polymorphisms (ApaI, BsmI, FokI, TaqI) in VDR have been widely evaluated to determine their association with IBD, and the results of these evaluations are often inconsistent.Therefore, we conducted a meta-analysis to shed some light on this issue and explored the sources of the heterogeneity between studies.We identified six articles for ApaI (cases/controls: 1902/1468), eight for TaqI (3053/2145), and five each for BsmI (1512/1616) and FokI (2315/1676).Data were analyzed under the random-effects model, and heterogeneity was explored by subgroup analyses.Overall, except for TaqI in allelic comparison [odds ratio (OR) = 0.90, 95% confidence interval (CI): 0.83-0.98],ApaI, BsmI, and FokI polymorphisms showed no significant associations with IBD across different genetic models of inheritance.However, subgroup analyses indicated significance for the association of ApaI with Crohn's ©FUNPEC-RP www.funpecrp.com.